Phenotypic integration in three Lamium species’ response to light and density - Barišić Klisarić, Nataša; Miljković, Danijela; Avramov, Stevan; Živković , Uroš; Tarasjev, Aleksej (Archives of Biological Sciences, 2021)
Paper description: The potential for evolutionary change depends on single traits and their relationships. Phenotypic integration is modified by natural selection but can also restrain evolutionary changes and is higher under environmental stress. We estimated phenotypic integration in annual Lamium purpureum and perennial Lamium album and Lamium maculatum during transplantation and under density and light treatments. Perennial species had similar correlation structures and subsequently became more similar to L. purpureum. The density effects in L. purpureum were habitat- and population-specific. Phenotypes became more integrated during ontogeny. Dissimilarities in phenotypic correlations were connected to ecological rather than to phylogenetic differences. Abstract: Phenotypic correlations were calculated and the levels of phenotypic integration of three congeneric species, annual Lamium purpureum and perennial Lamium album and Lamium maculatum, were estimated. Calculations were performed separately for different stages of development during transplantation under different density and light treatments. L. purpureum exhibited greater integration in comparison to the other two species before exposure to environmental treatments, as well as greater variability in phenotypic correlations in response to light and density. The perennial species possessed similar correlation patterns in comparison to annual L. purpureum, becoming more similar to L. purpureum at later stages of development. The effects of density and light intensity were dependent on the specific combination of factors, as well as on the species under study. Density effects in L. purpureum were also habitat- and population-specific. A greater difference in response to density treatments between habitats than between populations was detected. Overall, phenotypes become more integrated during ontogeny, while dissimilarities in phenotypic correlations among species and between populations were more related to ecological than to phylogenetic differences.